Characterization and application of torrefied Malaysia biomass as a biofuel for gasification - Fakhrur Razil Alawi, Abdul Wahid (2019)
Abundances of oil palm waste from palm oil industry and forestry residue from logging activity leads to disposal problems. However these waste can be used as a renewable energy resources and can be upgraded to tackle biomass disadvantages through torrefaction process. Torrefaction is a process of heating at low temperature ranging from 200 – 300 °C under inert condition. Pre-treated biomass with torrefaction consequently upgrades the properties of biomass making it suitable for gasification. Different group of biomass have different properties thus it is essential to study the biomass characteristic. For biofuel, higher heating value (HHV) is important and the process to determine HHV is time consuming and prone to errors. This problem could be solved by introducing HHV correlations. Thus, the objectives of this study are to investigate the effect of torrefaction process at different temperatures and residence time for several types of biomass, to estimate correlations of higher heating value based on chemical properties of the biomass, and to apply biomass gasification using raw and torrefied biomass. The sources of biomass are from oil palm waste (oil palm frond, empty fruit bunch, palm mesocarp fibre and palm kernel shell) and forestry residue (meranti, seraya, kulim and chengal sawdust). Biomass torrefaction process was conducted in a tubular reactor at four different temperatures (240, 270, 300 and 330 °C), in an inert nitrogen atmosphere at three different residence time (15, 30 and 60 minutes). The torrefied biomass products were characterized in terms of heating value, mass and energy yield, proximate and ultimate analysis. The obtained data were then used to estimate the higher heating value correlations and served as the starting information for a fluidized bed gasification simulation run. Based on the result of mass and energy yields, the optimum residence time used for both biomass are at 30 minute. From the ultimate analysis, the carbon composition for both oil palm waste and forestry residue show an increasing trends while hydrogen and oxygen compositions for both types of biomass show decreasing trends. From proximate analysis, fixed carbon is increased up to 56 wt% for oil palm waste and 47 wt% for forestry residue. For hydrogen to carbon and oxygen to carbon ratios, it showed a decreasing trend. The higher heating value increased as the enhancement factor for HHV reached up to 1.58 and 1.41 for oil palm waste and forestry residue respectively. On model development for the prediction of higher heating value, linear correlation based on proximate analysis gives the best estimate for oil palm waste (average absolute error (AAE): 5.37%) and forestry residue (AAE: 10.37%). Through gasification simulation, it is noted that the best biomass to be used from oil palm waste is oil palm frond (OPF) while for forestry residue is Kulim sawdust. Further analysis shows that both biomass produced the highest hydrogen gas when it is operated at gasification temperature of 700 °C, air to biomass ratio (ABR) of 0.2 and steam to biomass ratio (SBR) of 1.0. Using this operating condition, cold gas efficiency (CGE) and lower heating value (LHV) of the syngas are calculated. CGE changes for OPF is in the range of 0.85% to 6.29%, while for Kulim sawdust, the increment is from 3.0% to 8.6%.Both biomass have almost similar LHV except for the biomass at raw condition, torrefied at 240 °C and torrefied at 270 °C. Kulim sawdust shows a higher LHV than OPF with the different of 0.01 MJ/kg. By comparing both types of biomass (OPF and Kulim sawdust), Kulim sawdust is chosen to be the best biomass to be gasified under torrefied condition.